Foliar application of auxin on forage grasses subjected to salt stress - Sousa , Gilmara Matias de; Alvarez-Pizarro, Juan Carlos (Seven Editora, 2023)
Urochloa brizantha and Megathyrsus maximus grasses are species that are not very tolerant to salinity and that plant hormones are fundamental for the adaptation of plants to salinity, as they mediate several adaptive responses; the present work aims to evaluate the effect of auxin, indoleacetic acid, on the mechanisms of adaptation to salt stress. On the day of collection, the groups of plants were divided into leaves, stems and roots to estimate the contents of Na+ and K+ ions. The quantification of ions in these samples was done by flame photometry. Treatment with auxin did not stimulate the regulatory mechanisms of Na+ homeostasis in U species. brizantha and M. maximus. DOI:https://doi.org/10.56238/sevened2023.006-049